Immune-mediated lung diseases: A narrative review - Sweis, Jaleel Jerry G.; Sweis, Nabil W. G.; Alnaimat, Fatima; Jansz, Jacqueline; Liao, Ting-Wei Ernie; Alsakaty, Alaa; Azam, Abeera; Elmergawy, Hesham; Hanson, Hali A.; Ascoli, Christian; Rubinstein, Israel; Sweiss, Nadera (Frontiers in Medicine, 2023)
The role of immunity in the pathogenesis of various pulmonary diseases, particularly interstitial lung diseases (ILDs), is being increasingly appreciated as mechanistic discoveries advance our knowledge in the field. Immune-mediated lung diseases demonstrate clinical and immunological heterogeneity and can be etiologically categorized into connective tissue disease (CTD)-associated, exposure-related, idiopathic, and other miscellaneous lung diseases including sarcoidosis, and post-lung transplant ILD. The immunopathogenesis of many of these diseases remains poorly defined and possibly involves either immune dysregulation, abnormal healing, chronic inflammation, or a combination of these, often in a background of genetic susceptibility. The heterogeneity and complex immunopathogenesis of ILDs complicate management, and thus a collaborative treatment team should work toward an individualized approach to address the unique needs of each patient. Current management of immune-mediated lung diseases is challenging; the choice of therapy is etiology-driven and includes corticosteroids, immunomodulatory drugs such as methotrexate, cyclophosphamide and mycophenolate mofetil, rituximab, or other measures such as discontinuation or avoidance of the inciting agent in exposure-related ILDs. Antifibrotic therapy is approved for some of the ILDs (e.g., idiopathic pulmonary fibrosis) and is being investigated for many others and has shown promising preliminary results. A dire need for advances in the management of immune-mediated lung disease persists in the absence of standardized management guidelines.